Analisis Semiotika Pada Puisi “Bunga dan Tembok” Karya Wiji Thukul (Jurnal Sosial Humaniora dan Pendidikan, 2023)
This study aimed to rebuild the sense of nationalism that has started to fade as a result of the rapid development of the era. Undeniably, right now, most of the people prefer to share their ideas in social media and perhaps only a few who create their ideas into a useful work. Basically, an idea turns into a written work such as poem can be used as a motivation for other people. In fact, in new order regime when the nation’s youth got their right seized and all their activities limited, many people were against that. But, not as brave as Wiji Thukul who stand bravely fighting all the injustice. Wiji deployed literature in his fight, using words to evoke the spirit of the nation’s youth at that time. Just like in his poem entitle “Bunga dan Tembok” (warning). Up until now, the poem is still popular because of the meaning that represent the feeling of the people who feel the unfairness of the country. The poem was intended for dictator who seize people’s right. In conclusion, poem can be used as a weapon, and a literature work depend on how it is delivered and written.